Improving the Rumen Molar Proportion of Glucogenic Volatile Fatty Acids with the Inclusion of Siam Weed (Chromolaena odorata) Meal in Pelleted Diet of Fattened Cattle - Mullik, M. L.; Dato, T. O. D.; Mulik, Y. M.; Oematan, G. (Faculty of Animal Science, IPB University, 2024)
The objective of this metabolism study was to evaluate the efficacy of Siam weed (Chromolaena odorata) meal in pelleted diets for fattened cattle. Four 2-year-old Bali steers were assigned to four dietary treatments using a 4x4 Latin square experimental design. The treatments were pellets containing chromolaena meal at 10% (10COM), 20% (20COM), 30% (30COM), or 40% (40COM). The pellet was given at 2% liveweight (LW), and kume (Sorghum plumosum var. Timorense) grass hay was offered ad libitum. The diets were isonitrogenous (20%) and energy (11.5 MJ ME/kg DM). Dietary intake, digestibility, and rumen fermentation were the variables measured. The results showed that increasing chromolaena meal to 40% substantially decreased the nutrient intake. Dry matter intake decreased from 2.5% LW in the 10COM to 2.19% LW in the 40COM. Likewise, crude protein intake decreased from 749 g/d (10COM) to 661 g/d (40COM). On the contrary, digestibility, rumen pH, ammonia concentration (116–125 mg/dL), and volatile fatty acids were not affected. It might be concluded that chromolaena can be used as a protein source for ruminants, but at high levels of inclusion (40%) tends to reduce intake.